2001
DOI: 10.4141/a00-077
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gonadotrophin releasing hormone in prostaglandin F-based timed insemination programs for beef cattle

Abstract: R. 2001. The effects of gonadotrophin releasing hormone in prostaglandin F 2α α -based timed insemination programs for beef cattle. Can. J. Anim. Sci. 81: 335-343. Trials were conducted in the spring (May; n = 324) and fall (October; n = 132) with crossbred continental-type beef cows assigned on the basis of parity and postpartum interval to one of three timed-AI treatments and one of two post-AI treatments. The timed-AI treatments were: (DPG) double (14 d apart) PGF 2α (Lutalyse ® ) and AI (day = 0) 72 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…In agreement with other studies using similar protocols in suckled beef cows (Geary et al 1998;Martinez et al 2000;Small et al 2001) both the OVS and CIDR protocols resulted in a high degree of ovulation synchrony, with acceptable TAI pregnancy rates. This appeared to hold true over a range of postpartum ME intakes.…”
Section: Effect Of Synchronization Protocol On the Proportion Pregnantsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with other studies using similar protocols in suckled beef cows (Geary et al 1998;Martinez et al 2000;Small et al 2001) both the OVS and CIDR protocols resulted in a high degree of ovulation synchrony, with acceptable TAI pregnancy rates. This appeared to hold true over a range of postpartum ME intakes.…”
Section: Effect Of Synchronization Protocol On the Proportion Pregnantsupporting
confidence: 91%
“…To attain acceptable TAI pregnancy rates, ovulation must be highly synchronous and should occur on or around the day of insemination (Small et al 2001). To achieve this, truncation of the randomly staged follicular waves, and the induction of new, synchronous follicular waves must occur approximately 1 wk before the synchronous ovulation is required, so dominant follicles in all cows reach maturity at approximately the same time.…”
Section: Effect Of Synchronization Protocol On the Proportion Pregnantmentioning
confidence: 99%
“…The TAI pregnancy rates in these studies seemed generally comparable to those reported previously (Pursley et al 1997;Small et al 2001;Johnson and day 2004;Lamb et al 2006), except for the somewhat lower pregnancy rates in Herd A in exp. 3.…”
Section: Pregnancy Ratessupporting
confidence: 87%
“…Mots clé s: Pre´-synchronisation, gonadotrophine chorionique e´quine, GnRH, inse´mination artificielle a`pe´riode fixe, progeste´rone Current gonadotropin releasing hormone (GnRH)-based synchronization protocols for fixed-time AI (TAI) of cattle (Pursley et al 1995;Small et al 2001) typically consist of two GnRH treatments 9 d apart, with prostaglandin F 2a (PGF) 7 d after the first GnRH, and TAI either 16 to 18 h after the second GnRH (Ovsynch), or concurrent with the second GnRH (COSynch). Pregnancy rates have been lower in heifers than cows subjected to these protocols (Pursley et al 1997;, but were generally improved in heifers by inseminating those observed in estrus prior to scheduled TAI (Johnson and Day 2004).…”
mentioning
confidence: 99%
“…Both are PGF 2α -based protocols modified to synchronize the development of the ovulatory follicle as well as ovulation. The Ovsynch procedure uses an initial injection of GnRH to synchronize follicular wave emergence and a second GnRH to synchronize ovulation (Pursley et al 1995;Hirad et al 1999;Small et al 2001). The CIDR protocol uses an initial injection of progesterone and estradiol-17β and an intravaginal progesterone-releasing device to synchronize follicular wave emergence and a second estradiol-17β to synchronize ovulation (Martinez et al 2000).…”
mentioning
confidence: 99%